Biological calcium carbonate with a unique organic–inorganic composite structure to enhance biochar stability. Issue 11 (5th October 2021) - Zhang, Jiawei; Wu, Can; Hou, Wenjing; Zhao, Qidi; Liang, Xin; Lin, Shengwei; Li, Huabin; Xie, Yanhua
Abstract : The inorganic components in Bio-CaCO3 catalyze the deoxygenation of biochar and increase the degree of aromatization of the carbon matrix. The stable pyridinic-N structures are doped into the carbon skeleton, which further improves the stability of biochar. Abstract : Biochar stability is a key factor affecting the efficiency of soil carbon sequestration. Mineral calcium carbonate (M-CaCO3 ) can enhance the stability of biochar, and the mechanism has been extensively studied; however, similar studies on biological calcium carbonate (Bio-CaCO3 ), another natural form of calcium carbonate, are lacking. In this work, Bio-CaCO3 was used as an additive to explore the mechanism by which it enhances the stability of biochar. The results showed that Bio-CaCO3 improved the stability of biochar at pyrolysis temperatures ranging from 250 to 700 °C, and the enhancement effects increased upon increasing the pyrolysis temperature. The enhancement effects of M-CaCO3 were better at lower temperatures (250 and 400 °C) while Bio-CaCO3 was better at higher temperatures (550 and 700 °C). Mechanistic studies showed that the enhanced stability of Bio-CaCO3 at 250 °C was due to the fact that the inorganic component in Bio-CaCO3 promoted the deoxidation of the carbon matrix and the aromatization of aliphatic carbon at 400 °C. The reasons for the increased stability using Bio-CaCO3 at high temperatures included two mechanisms. One is that the inorganic components in Bio-CaCO3 promoted the aromatization of the carbon matrix. The other is that the unique organic nitrogen-containing functional groups in Bio-CaCO3 underwent dimerization and cyclization with the organic carbon components in biomass to form a more stable pyridinic-N structure. This work provides novel ideas for enhancing biochar stability using Bio-CaCO3 .